2006
DOI: 10.1002/rmv.517
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of congenital CMV infection via dried blood spots

Abstract: Cytomegalovirus (CMV) infection is the most frequent congenital infection in humans and can cause permanent damage--particularly neurological--in about 20% of those infected, with or without symptoms at birth. Laboratory diagnosis is essential on account of the relatively non-specific clinical manifestations in symptomatic newborns but also because of the high frequency of asymptomatic cases that are nevertheless at risk of lesions later in life. However, these tests need samples taken within 3 weeks of birth … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
82
0
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(87 citation statements)
references
References 28 publications
3
82
0
1
Order By: Relevance
“…Since then several studies tested and adapted this method, with sensitivity ranging from 71% to 100% and specificities of 99% to 100%. 54 A recent study found much lower sensitivities, near 34%, when DBS were used as screening test. 55 However, it is the only way to detect a cCMV infection retrospectively.…”
Section: Retrospective Approachmentioning
confidence: 97%
See 1 more Smart Citation
“…Since then several studies tested and adapted this method, with sensitivity ranging from 71% to 100% and specificities of 99% to 100%. 54 A recent study found much lower sensitivities, near 34%, when DBS were used as screening test. 55 However, it is the only way to detect a cCMV infection retrospectively.…”
Section: Retrospective Approachmentioning
confidence: 97%
“…Cross-contamination of adjacent stored cards has been reported. 54,[59][60][61] To understand the importance of cCMV as a cause of childhood hearing loss, we reviewed studies that conducted retrospective testing in a group of hearingimpaired children. Requirements were testing by real-time PCR for quantitative analysis of CMV DNA on DBS or on dried umbilical cords.…”
Section: Retrospective Approachmentioning
confidence: 99%
“…Dried blood spots (DBS), or Guthrie cards, which are collected routinely at birth in certain countries for newborn genetic and metabolic diseases screening, can be stored for extended periods of time. Since CMV DNA is stable on such DBS cards for up to 18 years, they offer an attractive tool for the retrospective molecular diagnosis of congenital infection in individual children who present with delayed-onset sequelae (112)(113)(114)(115). DBS also have appeal for use in newborn congenital CMV screening programs.…”
Section: Advances In Diagnosis and Management Of The Newbornmentioning
confidence: 99%
“…DBS also have appeal for use in newborn congenital CMV screening programs. However, the variable and disappointing rates of detection of CMV DNA (34 to 100%) have made DBS unsuitable for these purposes (112,114,(116)(117)(118)(119)(120)(121)(122), possibly because not all newborns are viremic at birth or due to technical factors (118,(122)(123)(124). However, a positive DBS PCR finding is diagnostic of congenital CMV infection and accordingly can be useful to retrospectively diagnose congenital CMV infection beyond the neonatal period.…”
Section: Advances In Diagnosis and Management Of The Newbornmentioning
confidence: 99%
“…DBS testing has been proposed as an alternative method of microbiologic analysis for different infections, since it presents many advantages, such as minimal invasiveness of sampling, relative ease of collection, the possibility of storage for long periods, and a good agreement with serum or plasma testing (12)(13)(14)30). Many studies have evaluated the diagnostic potential of DBS cards testing for retrospective diagnosis of congenital infections during childhood, in particular those due to cytomegalovirus (31,32).…”
Section: Discussionmentioning
confidence: 99%